JavaScript & jQuery : interactive front-end web development - Duckett, Jon, ....- (Indianapolis : Wiley, 2014)
This full-color book adopts a visual approach to teaching JavaScript & jQuery, showing you how to make web pages more interactive and interfaces more intuitive through the use of inspiring code examples, infographics, and photography. The content assumes no previous programming experience, other than knowing how to create a basic web page in HTML & CSS. You'll learn how to achieve techniques seen on many popular websites (such as adding animation, tabbed panels, content sliders, form validation, interactive galleries, and sorting data)..
Keywords: Javascript; Jquery; Software